Silver eyes : five nights at freddy$1 (Bss - Cawthon, Scott; Wrisley, Kira Breed (New york : Scholastic, 2016)
From the creator of the bestselling horror video game series Five Nights at Freddy's.
Keywords: Five Nights at Freddy's.